2010
DOI: 10.1159/000319796
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Induces Differentiated Contractile Responses in Porcine Pulmonary Arteries and Veins

Abstract: Background/Aims: Sepsis-induced lung injury is characterized by pulmonary hypertension, edema and deteriorated gas exchange. As in vivo studies have indicated that bacterial endotoxin predominantly induces a pulmonary venous constriction, we aimed to investigate effects of endotoxin on isolated porcine pulmonary vessels. Methods: Pulmonary arteries and veins were examined using in vitro isometric force recordings. Endothelin-receptor protein expression and distribution were analyzed by Western blot and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…They aimed to recreate acute lung injury in a rat model to study the recovery, complications, and mortality associated with early sepsis. Patients with acute lung injury and acute respiratory distress account for a sizeable portion of intensive care cases and are at risk of sepsis [32][33][34][35][36]. In this study, sepsis was induced by intra-peritoneal administration of bacterial lipopolysaccharide from E. coli.…”
Section: Hif-1 In the Lungsmentioning
confidence: 99%
“…They aimed to recreate acute lung injury in a rat model to study the recovery, complications, and mortality associated with early sepsis. Patients with acute lung injury and acute respiratory distress account for a sizeable portion of intensive care cases and are at risk of sepsis [32][33][34][35][36]. In this study, sepsis was induced by intra-peritoneal administration of bacterial lipopolysaccharide from E. coli.…”
Section: Hif-1 In the Lungsmentioning
confidence: 99%
“…For example, one study showed that endotoxin increased contraction of intrapulmonary veins and augmented the filtration pressure in the pulmonary capillaries leading to PE in pigs (Persson et al . ). On the other hand, although changes in pulmonary artery structure and function during the development of PH have been extensively described, there is an increasing awareness of defective pulmonary venous tone in PH.…”
Section: Introductionmentioning
confidence: 97%
“…We noted an increased peak inspiratory pressure (PIP) in several LPS-exposed animals, again with a tendency of less rise in the double treatment ( Table 1 ). A rise in airway pressure could be a sign of an inflammatory response in lung tissue and is a hallmark of acute lung injury [22] . Acute kidney injury (AKI), signified by polyuria or oliguria plus elevated creatinine, urea, and decreasing Base Excess, was noted in many animals exposed to LPS.…”
Section: Discussionmentioning
confidence: 99%